Pengaruh Penambahan Karbon Dan Nitrogen Terhadap Mikrostruktur, Kekuatan Tarik Dan Mampu Bentuk Paduan Co-28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni [Influence of Additional Carbon And Nitrogen on Microstructure, Tensile Strength And Workability of Co- 28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni] - Rokhmanto, Fendy; Soegijono, Bambang; Kartika, Ika (Jurnal Metalurgi, 2016)
Co-Cr-Mo alloys are widely used as bone and dental implant materials, where the composition of the alloy refers to the standard ASTM F75. Co-Cr-Mo alloys has good mechanical properties, biocompatibility and high corrosion resistance. Objective of this paper is to investigate the influence of Carbon and Nitrogen on tensile strength and workability of Co-28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni when used to that applications. Carbon is added into the alloys of 0.08; 0.15 and 0.25 (% weight), whereas nitrogen at 0.2 (% weight). As cast ingot homogenized at 1200 °C for 6 h, and then hot rolled with preheating 1200 °C for 1 h and then water quenched. The alloys (as cast and after hot rolling) were characterized with optical microscope and SEM to investigate the microstructure and the tensile test to investigate the mechanical properties and fraktografi. The tensile strength of the alloy Co-28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni increased with the addition of carbon in the alloy, while the addition of nitrogen increased work ability of Co-28Cr-6Mo-0,8Si-0,8Mn-0,4Fe-0,2Ni alloy.